Fecal microbiota transplantation reverses insulin resistance in type 2 diabetes: A randomized, controlled, prospective study - Wu, Zezhen; Zhang, Bangzhou; Chen, Fengwu; Xia, Rongmu; Zhu, Dan; Chen, Baolong; Lin, Aiqiang; Zheng, Chuyan; Hou, Ducheng; Li, Xiaoyu; Zhang, Shuo; Chen, Yongsong; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Objectives Recent studies have shown that fecal microbiota transplantation (FMT) improved the metabolic profiles of patients with type 2 diabetes mellitus (T2DM), yet the effectiveness in reversing insulin resistance and increasing metformin sensitivity in T2DM patients have not been reported. In this study, we evaluated the improvements of T2DM patients and their gut microbiota by FMT alone and FMT plus metformin. Methods A total of 31 patients with newly diagnosed T2DM were randomized to intervention by metformin, FMT, or FMT plus metformin in the study. Patients were followed up at baseline and week 4 after treatment. Blood and stool samples were collected and subject to analyze clinical parameters and microbial communities by metagenomic sequencing, respectively. Results FMT alone and FMT plus metformin significantly improved the clinical indicators HOMA-IR and BMI in T2DM, besides fasting blood glucose, postprandial blood glucose, and hemoglobin A1c that were also controlled by metformin. Donor microbiota effectively colonized in T2DM with slightly higher colonization ration in FMT than FMT plus metformin within 4 weeks, resulting in increased microbial diversity and community changes from baseline after treatment. A total of 227 species and 441 species were significantly alerted after FMT and FMT plus metformin, respectively. FMT were significantly associated with the clinical parameters. Among them, Chlorobium phaeovibrioides, Bifidibacterium adolescentis and Synechococcus sp.WH8103 were potential due to their significantly negative correlations with HOMA-IR. Conclusions FMT with or without metformin significantly improve insulin resistance and body mass index and gut microbial communities of T2DM patients by colonization of donor-derived microbiota.